A study of physicians' experiences with recommending HPV vaccines to adolescent boys. (3rd October 2017) - Wong, Li Ping; Edib, Zobaida; Alias, Haridah; Mohamad Shakir, Sharina M.; Raja Muhammad Yusoff, Raja N. A.; Sam, I-Ching; Zimet, Gregory D.
Abstract: Assessing physicians' experiences in HPV vaccine recommendation and delivery to adolescent boys is essential to providing an understanding of the issues of vaccine acceptance and an insight for policymakers to enhance HPV vaccinations among adolescent boys. Between January and April 2014 a mail survey was conducted using physicians in Malaysia known to provide either one or both HPV vaccine (Gardasil and Cervarix) immunisation services. A total of 357 completed questionnaires were received (response rate 22.5%). Of these, 335 physicians see adolescent boys aged 11 to 18 years old in their practice. Only 26.3% ( n  = 88) recommended the HPV vaccine to these boys. A total of 46.6% ( n  = 41) have successfully given the HPV vaccine to adolescent boys. A lack of proper guidelines from the health authorities regarding the recommendation of HPV vaccine to the boys (37.2%) and a lack of awareness of the availability of the vaccine for boys (32.8%) were the most commonly cited reasons for non-recommendation. Impact statement: Recommending the HPV vaccine for adolescent boys remains a challenge for physicians. Our study provides evidence of challenges and barriers faced by Malaysian physicians who recommend the HPV vaccines (Gardasil and Cervarix) in their practices. In this study, physicians reported HPV vaccine uptake by adolescent boys was very poor. A lack of proper guidelines from the health authorities regarding the recommendation of HPV vaccine to boys and a lack of awareness of the availability of the vaccine for boys were the most commonly cited reasons for non-recommendation. Physicians viewed that support and encouragement from the health authorities are needed to promote the recommendation of the HPV vaccine to adolescent boys. Physicians were also of the opinion that the lay public should be educated about the availability of the HPV vaccine for boys, and its benefits, safety and efficacy, and the high susceptibility of boys to getting HPV infections. The findings provide insights that could be helpful to policymakers or high-level decision-makers of the potential strategies to enhance HPV uptake among adolescent boys.